Modernisasi Sektor Perikanan Bantaeng dan Dampaknya terhadap Kehidupan Nelayan Tradisional - Alta’ir Rachmat Hidayat; Darwis Darwis; Imam Fadhil (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Bantaeng Regency, South Sulawesi, has great potential in the fisheries sector thanks to its vast coastline and abundant marine resources. The modernization of the fisheries sector in this area includes the application of the latest technology, infrastructure development, and training for fishermen. The modernization program implemented by the government aims to increase the productivity and welfare of fishermen, by introducing more efficient fishing gear, such as motorized machines and modern nets. The results of the study show that this change has succeeded in increasing fish catches and fishermen's income. In addition, the construction of modern fish processing facilities and training programs have supported the sustainability of the fisheries sector. This modernization has a positive impact on the economy of coastal communities, but it also presents challenges in terms of income inequality and environmental sustainability. This study concludes that the modernization of the fisheries sector in Bantaeng has the potential to strengthen the local economy while preserving marine resources.